Director's report of research in Kansas 2008 - Kansas State University. Agricultural Experiment Station (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
The 2008 Director’s Report of Research in Kansas provides a list of journal articles, station publications, and other published manuscripts from scientists in our departments, centers, fields, and associated programs.
DRR08
On cover: July 1, 2003 to June 30, 2008
Keywords: Kansas; Agricultural Experiment Station; Research; Publications; Finances; Projects